Keep it or kill it? The optimal management of old technology-based products in the prevalence of new technology-based products. Issue 12 (2nd December 2021) - Liu, Xiaoxi; Kim, Byung Cho
Abstract: With fast-moving technological innovation, technology firms are confronted with the issue of how to dispose of the old technology-based product. Regarding the old technology-based product's response strategy to a prevalent new technology-based product, firms usually choose from the three options of stopping, maintaining, and improving. We consider a multiproduct monopolist that manufactures traditional, tangible goods derived by old and new technologies, respectively, and build a two-period analytical model to form the response strategy for the old technology-based product. We also investigate the action sequence about whether to stop or improve the old product before or after network externality arises in the market, and determine the level of improvement effort exerted on the old product. The results show that the firm should maintain the old product if the new product is significantly superior to the old one. Furthermore, when the new product is superior to the old one, the firm has an incentive to stop or improve the old product based on the quality difference between old and new products and the marginal production cost of the old product. Finally, we prove that the improvement of old products can increase demands for both old and new products under specific conditions.